2004
DOI: 10.1161/01.cir.0000138198.62961.41
|View full text |Cite
|
Sign up to set email alerts
|

On-Pump Versus Off-Pump Coronary Artery Bypass Surgery in a Matched Sample of Women

Abstract: Background-Women have consistently higher mortality and morbidity than men after coronary artery bypass grafting (CABG). Whether elimination of cardiopulmonary bypass and performance of coronary artery bypass grafting off-pump (OPCAB) have a beneficial effect specifically in women has not been defined. Methods and Results-From January 1998 through March 2002, 21 902 consecutive female patients at 82 hospitals underwent isolated CABG, as reported in an administrative database. Propensity score computer matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…The inclusion criteria were applied to the 94 studies assessed, but only nine articles were selected and evaluated in details. These were all published studies, of which clinical characteristics are shown in Table 1 [42][43][44][45][46][47][48][49][50] .…”
Section: Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion criteria were applied to the 94 studies assessed, but only nine articles were selected and evaluated in details. These were all published studies, of which clinical characteristics are shown in Table 1 [42][43][44][45][46][47][48][49][50] .…”
Section: Selected Studiesmentioning
confidence: 99%
“…Mortality was reported in seven studies (23,163 patients, Figure 1) 42,[44][45][46][47][48]50 and according to the analysis, it was significantly lower in off-pump group (OR = 0.82, 95%CI: 0.70 -0.98, p = 0.03), with heterogeneity regarding the overall effect in the sample (Chi 2 = 24.51, p = 0.0004). The OR represents a 18% reduction in the mortality risk in favor of the OPCABG surgical technique and must be considered with care in the context of the heterogeneity among the studies mentioned above.…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 16,871 consecutive women comparing off‐pump and on‐pump CABG surgery demonstrated that those who underwent off‐pump surgery had a better clinical outcome with reduced mortality, respiratory complications, and length of hospital stay [28]. Similarly, a more recent study investigated 7,376 women undergoing CABG surgery [29]. Compared to a propensity‐matched sample of females who underwent off‐pump CABG surgery, women who underwent conventional CABG surgery had a 73% higher mortality rate, and a 47% higher complication rate due to bleeding.…”
Section: Bleeding and Access Site Complicationsmentioning
confidence: 99%
“…In an effort to minimize the CPB-induced abnormalities associated with coronary artery bypass grafting, especially those due to biocompatibility of bypass circuits, surgeons have eliminated the bypass circuit by using direct coronary artery revascularization on the beating heart (OPCAB). Comparisons of postoperative bleeding in on-pump procedures versus OPCAB have usually [125,155,162,187], but not always [76,92], shown reduced levels of bleeding after OPCAB. Interestingly, Lo and co-workers found that the despite heparinization, CABG surgery with CPB (ONCAB) was associated with excessive thrombin generation and fibrinolytic activity immediately after surgery, but OPCAB group demonstrated a delayed postoperative response that became equal in magnitude to the ONCAB in the later (20-96 h) postoperative period [123].…”
Section: Biocompatible Synthetic Surfacesmentioning
confidence: 99%